An Unusual Presentation of Systemic Lupus Erythematosus as Evan Syndrome: A Case Report and Review Literature: Evans Syndrome Associated with Systemic Lupus Erythematosus in an Adult: A Case Report and Literature Review. Issue 1 (11th July 2018) - Al Bshabshe, Ali; Al-Shehri, Hamdan; Assiri, Ali; Jamil, Abdulmoneim
Evans syndrome is a rare autoimmune disorder with an unknown etiology. In this paper, we report the case of a 32-year-old Saudi woman living with Evans syndrome for more than 8 years (post-splenectomy) who was also diagnosed with systemic lupus erythematosus (SLE). She was admitted to our Hospital with severe headache and confusion due to cerebral venous thrombosis. The major hematologic manifestations of SLE were pancytopenia and the antiphospholipid syndrome, which are indicators of disease activity when all other possible causes are excluded. The patient was treated with anticoagulation and immunosuppressive therapy and subsequently showed significant improvements in thrombosis, thrombocytopenia, and anemia. This case report provides an overview of the association between Evan syndrome and SLE.